New firm formation and its effect on employment growth in declining regions - Heike Delfmann; Sierdjan Koster (European Regional Science Association (ERSA), 2014)
New firm formation is often highly prioritized by local governments, particularly for regions that are declining. Entrepreneurship can play an important role in keeping declining regions vital through job creation. Yet, the way in which new firm formation exerts its influence on employment growth is not yet evident. Are start-ups in those areas equally productive in influencing employment change as they are in growing regions? Although there is a large and growing body of research on new firm formation and employment, there is still a knowledge gap concerning the impact of the context on the effect of new firm formation. Previously the focus has been on growth. New firm formation can contribute direct and indirectly to regional employment. The indirect effects are thought to have a larger impact on the long term, and indirect effects are not per sé positively related to employment growth. Focusing on the regional context, we investigate whether the relationship differs depending decline or growth, and by the degree of urbanization, to determine both long and short term employment effects. In order to establish the impact of new firm formation on employment rates, the paper examines panel data of firm dynamics and employment growth retrieved from the LISA database covering the whole of the Netherlands on a municipality level (418 regions) between 1996-2010. This data is complemented with data on population density, size, growth and decline from the Statistic Netherlands.
Keywords: M13; R11; O18; 330; Employment growth; population decline; new firm formation; urban and rural regions; direct and indirect effects